2022
DOI: 10.3390/f13060948
|View full text |Cite
|
Sign up to set email alerts
|

Audio-Visual Preferences for the Exercise-Oriented Population in Urban Forest Parks in China

Abstract: The purpose of this study is to explore the audio-visual preferences of exercisers in urban forest parks in China and to make practical suggestions for park landscape design. Taking Beigushan Forest Park in Lianyungang City, Jiangsu Province as a case, based on field research and questionnaire survey, this study analyzed the audio-visual preference characteristics of exercisers in the park, revealed the correlation between audio-visual preference and exercisers’ behaviors and individual characteristics, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
2
0
0
Order By: Relevance
“…People are most active where grasslands, water features, and woodlands coexist and where the accessible-but-not-encouraged spaces dominate. Results not only confirmed the accuracy of the generated model but also were in line with existing evidence suggesting that activities, especially informal ones, can largely be influenced by individual preference ( Cheung, 2013 ; Cai et al, 2021 ; Xu et al, 2022 ). People continuously make minor modifications to the original arrangement of spaces, personalize their temporarily used spaces based on their needs and the rules of design, and thereby make these spaces their own ( Thwaites et al, 2013 ).…”
Section: Discussionsupporting
confidence: 87%
“…People are most active where grasslands, water features, and woodlands coexist and where the accessible-but-not-encouraged spaces dominate. Results not only confirmed the accuracy of the generated model but also were in line with existing evidence suggesting that activities, especially informal ones, can largely be influenced by individual preference ( Cheung, 2013 ; Cai et al, 2021 ; Xu et al, 2022 ). People continuously make minor modifications to the original arrangement of spaces, personalize their temporarily used spaces based on their needs and the rules of design, and thereby make these spaces their own ( Thwaites et al, 2013 ).…”
Section: Discussionsupporting
confidence: 87%
“…People are most active where grasslands, water features, and woodlands coexist and where the accessible-but-notencouraged spaces dominate. Results not only confirmed the accuracy of the generated model but also were in line with existing evidence suggesting that activities, especially informal ones, can largely be influenced by individual preference (Cheung, 2013;Cai et al, 2021;Xu et al, 2022). People continuously make minor modifications to the original arrangement of spaces, personalize their temporarily used spaces based on their needs and the rules of design, and thereby make these spaces their own (Thwaites et al, 2013).…”
Section: Human Behavioral Responses and Their Component Visual-aural ...supporting
confidence: 83%
“…Our research collections focus on the experience of multisensory interactions in urban forests. Xu et al [8] analyzed the audio-visual preference characteristics of exercisers in a park, and found that the forest and its landscape and birdsong avenues are most preferred by exercisers, though the audio-visual preferences of people with different exercise forms differ. Then, they analyzed children's multi-sensory landscape preferences in a park and explored the influence of multi-sensory experiences on children's behavioral experience [9].…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%